History of Specialization in the U.S. Public Accountancy and the CPA Evolution Project - Pekdemir , Recep; Süer , Ayça Zeynep (Journal of Accounting and Finance, 2021)
The study has a three-fold purpose. First, it aims to examine the historical developments of the specialization efforts in the accounting profession. Second, a main goal is to review the features of the CPA Evolution that has been a joint project of the NASBA and the AICPA in the U.S. Furthermore, the study attempts to identify and discuss its advantages and disadvantages, challenges, and implications for educators and legislators. The paper argues that the CPA Evolution for the U.S. public accountancy has certain risks and threats, will be emerging initiative and inevitable within the profession, and seems to have formal transforming the CPA licensure.